Prevalence of health problems in suburban schools in Chennai, India - Kumar, Haritha S.; Pasupathy, Sekar; Chinnasami, Balaji; Ramraj, Balaji (International Journal of Contemporary Pediatrics, 2017)
Background: School health programmes help in early detection of health problems but the literature about its effectiveness in India is sparse. Hence, this study was undertaken. The aim of the present study is to measure the weight, height and BMI in school children and to interpret it using the IAP growth charts, to estimate the prevalence of stunting, undernutrition, overweight, obesity, refractory errors, hearing impairment and dental caries in children and to compare the prevalence of above parameters among gender and age. Methods: This is a cross sectional study, conducted between January to March 2017 in 3 suburban schools in Chennai, Tamil Nadu. A total of 631 children in the age group of 6-18 years were screened by an expert team. Weight and height was measured using standard equipments, BMI was calculated and plotted on IAP growth charts. Vision was tested using Snellen chart by an optometrist. Dental evaluation was done by a dentist and hearing screening done by an audiologist using puretone audiometry. Statistical analysis was done using Chi-square test, P value of <0.05 was considered as significant. Results: Out of 631 children, 344 were boys and 287 were girls. 507 children belonged to the primary age group (6-12 years) and 124 children belonged to the secondary age group (12-18 years). The prevalence of stunting was 0.7% and was gradually decreasing with increasing age. The overall prevalence of thinness, overweight and obesity was 10.1%, 1.5% and 7.1% respectively. Underweight was more common among the primary age group whereas obesity was more commonly seen in secondary age group. The prevalence of weight abnormalities in both the age groups and sexes were statistically significant. 19% children had visual defects and the prevalence was more in older children. Dental caries was more commonly seen in primary dentition and the prevalence was 18.9%. Due to lack of ambient conditions, only severe hearing impairment was detected. 5 (0.8%) children had severe hearing impairment. Conclusions: The burden of health problems like malnourishment, refractory errors, dental caries and hearing impairment are high in school children. With the results of the present study, we can conclude that there is a need for implementation of school health screening programmes to detect these health problems at an early stage. To bring a significant change in the community, a dedicated national school health screening program is needed